Locus Of Control, Transformative Leadership, Self Efficacy, Professional Commitment On The Ability To Detect Fraud. Auditor's Experience As Moderating Variables - Yohana Gabriella Natalia; Muhammad Nuryatno (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to investigate the influence of Locus of Control, Transformative Leadership, Self Efficacy, and Professional Commitment on the Ability to Detect Fraud with the audit experience as a moderator. The population in this research are auditors who work at Public Accounting Firms in DKI Jakarta. The sampling method used was an unknowns sample because the population size was uncertain, and the researcher could not obtain information regarding the number of accountants working at the Public Accounting Firm in DKI Jakarta. The number of respondents obtained for this research was 155 respondents. In this research, the analytical methods used are descriptive statistics, data feasibility testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. Test results prove that Locus of Control (LoC) has a positive effect on the ability to detect fraud, transformational leadership and professional commitment have no effect on the ability to detect fraud. Self-efficacy has a negative effect on the ability to detect fraud. Auditor experience moderates the influence of Locus of Control and Self Efficacy on the ability to detect fraud. Auditor experience does not moderate the influence of transformative leadership and professional commitment on the ability to detect fraud.